Prevalence of mental disorders among family members of individuals on the autism spectrum: systematic review and meta-analysis. - Lins-Silva, Daniel H.; Bandeira, Igor D.; Faria-Guimarães, Daniela; Dorea-Bandeira, Ingrid; Tolentino, Arthur; Miranda-Scippa, Ângela; Hermens, Daniel F.; Lucena, Rita (European Child & Adolescent Psychiatry, 2025)
Parenting a child on the autism spectrum presents particular challenges that can lead to increased stress, anxiety, and depression among family members. Therefore, we aimed to investigate the prevalence of mental disorders in first-degree relatives of individuals on the autism spectrum. This article adheres to the Preferred Reporting Items for Systematic Review and Meta-Analyses Protocols (PRISMA-P) guidelines, including studies indexed in PubMed/Medline, Embase, PsycINFO, Biblioteca Virtual em Saúde (BVS), and SciELO. Nineteen articles met eligibility criteria for the systematic review. Using a random-effects model (N = 93,876), we found a pooled prevalence of affective disorders of 13% in mothers of people on the autism spectrum (95% CI 7–21%; I2 = 99%, p < 0.01). Additionally, another random-effects model pointed out that first-degree relatives of people on the autism spectrum (N = 93,263) were more likely to present affective disorders than relatives of people with neurotypical development (N = 152,455) (pooled OR: 2.17; 95% CI 1.81–2.61). Careful assessment for mental disorders in parents and siblings of individuals on the autism spectrum is crucial to ensure appropriate treatment for these family members. This approach can also contribute to optimizing care for the individuals on the autism spectrum.